Duševne in spoznavne motnje pri Parkinsonovi bolezni - Danieli, Aljoša (Medicinski razgledi, 2004)
The article reviews cognitive impairment and mental disorders in Parkinson's disease, which often accompany movement disorders and contribute to patients disability. Specific clinical picture as well as pharmacological treatment of depression, anxiety, dementia, psychosis, and delirium in parkinsonism is described.
Keywords: Duševne motnje; Parkinson Disease; Parkinsonova bolezen; Diagnosis; Drug Therapy; Spoznavne motnje; Physiopathology; Delirij; Demenca; Cognition Disorders; Depresivna motnja; Mental Disorders; Nevroza obsesivno-kompulzivna; Aged; Dementia; Nevroze anksiozne; Psihoze; Depressive Disorder; Anxiety Disorders; Starostniki; Obsessive-Compulsive Disorder; Psychotic Disorders; Delirium